Relationship between personality types and cyber love addiction among students in a Malaysian public university - Naseri, Sousan (2016)
Cyber love Addiction (CLA) is a behaviour addiction that may happen through Facebook where individuals are seeking for online friends. The particular personality traits may lead individuals to seek for lover/lovers through Facebook which make a dependency to one or more than one love relationship that tracing the pattern of love addiction. This study aims to determine personality traits predictors of cyber love addiction among respondents by controlling gender and program cluster. There is 5-personality trait tested as in Big Five Personality traits – Extraversion, Agreeableness, Consciousness, Openness, and Neuroticism. The sample n=380 of UPM students who were randomly selected through Stratified Random Sampling as 35% male, 65% female, and 35% Social Science and 65%, Non Social Science students. The data was collected through a self-administered questionnaire which was adapted and adopted from Five Big Personality Trait (John and Srivastava, 1999). Bergen Facebook Addiction Scale (Andreassen et al.. 2012) and Love Addiction Scale (Aaron. 2010: Mellody & Carnes. 2005). A total number of 376 completed questionnaires received and analysed through SPSS as Descriptive Statistics (profile of respondents and RO₁). Independent Sample T-Test (RO₂ and RO₃). Pearson Correclation Test (R0₄). and Multiple Liner Regression (MLR) model (RO₅). The results of RO₁ showed that among all personality traits. Extraversion had the high mean score among all group of respondents by showed the higher mean score among female and Social Science respondents. As following the results of RO₁ also revealed that among all CLA dimensions Tolerance had the high mean score among all groups of respondents by showed the higher mean score among male and Non Social Science respondents. The finding of RO₂ demonstrated that there is no significant difference (p≥0.05) of personality traits among respondents. The results of RO₃ showed that CLA mean scores among male and female respondents were significantly difference (p≤0.05) in CLA score and 5-CLA dimensions (Self-Awareness. Tolerance. Withdrawal. Conflict and Relationship Experience). whereas there was significant difference (p≤0.05) between Social Science and Non Social cluster mean score in 2-CLA dimensions (Self- Awareness and Tolerance). The results of R0₄ showed that in all group of respondents at least there was one personality traits in each group of respondents that showed significant relationship (p≤0.05) with CLA and 7-CLA dimension. For RO₅. the validated IVs were selected to use in 8- Model of MLR (Y lCLA, Y₂sailence, Y₃Tolerance, Y4Self-Awareness, Y₅ withdrawal, Y₆ Mood Modification, Y₇Confilict and Y₈ Relationship Experience and The results obtained that among all personality traits only Neuroticism significantly (p≤0.001) predict CLA. The results showed the gender effect on CLA and all CLA dimensions expect Mood Modification, whereas program clusters only had effect on Salience and Self-Awareness. Therefore gender sensitive programs and gender awareness program have to be developed in order to address the issues of CLA and personality traits effectively.